(3GdNUGd aj GdCNdGbs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs
(3ChdgG (B:s
...(3agPG eG dG jLhR dCf eG dG KGfj dg dG jONd aj HGH GdCYOGO(B...s
(3BNQgG (B:s
... (3hjCcd dMhege hjcSQ YXege (B... (3CSO hPFH hKYdH hcdH hNfRjQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B274s
(3GdPQjYI(B:(3L(B7(3,U(B193(3,Qbe(B876s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs